2008
DOI: 10.1128/iai.01780-06
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Cytokines Is Detected in the Placentas of Cattle Infected withNeospora caninumand Is More Marked Early in Gestation When Fetal Death Is Observed

Abstract: The protozoan parasite Neospora caninum causes fetal death after experimental infection of pregnant cattle in early gestation, but the fetus survives a similar infection in late gestation. An increase in Th1-type cytokines in the placenta in response to the presence of the parasite has been implicated as a contributory factor to fetal death due to immune-mediated pathological alterations. We measured, using real-time reverse transcription-PCR and enzyme-linked immunosorbent assay, the levels of cytokines in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
80
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 46 publications
14
80
1
3
Order By: Relevance
“…Moreover, research about mice has shown that although, excessive levels of IFN-are deleterious for the establishment of pregnancy, uterine NK cell-derived IFNcontributes to a normal pregnancy and facilitates pregnancy-induced artery remodeling (Ashkar et al, 2000). The IFN-, as potential abortifacient, was significantly increased in LPS and parasite infection induced abortion (Rosbottom et al, 2008;Wang et al, 2011). In our study, the uterine IFN-levels significantly increased in LPS treated mice and in LPS interference endometrial cells.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Moreover, research about mice has shown that although, excessive levels of IFN-are deleterious for the establishment of pregnancy, uterine NK cell-derived IFNcontributes to a normal pregnancy and facilitates pregnancy-induced artery remodeling (Ashkar et al, 2000). The IFN-, as potential abortifacient, was significantly increased in LPS and parasite infection induced abortion (Rosbottom et al, 2008;Wang et al, 2011). In our study, the uterine IFN-levels significantly increased in LPS treated mice and in LPS interference endometrial cells.…”
Section: Discussionsupporting
confidence: 49%
“…The immune balance at the maternal-fetal interface IL-6, IL-10, IL-13, etc., (Wilczy ski, 2005). The Th1/Th2 cytokine balance was destroyed when the pregnancy failure occurred, especially under abnormal situations, deviated towards Th1 activity demanding the IFN-, IL-12 and TNF- (Zhong et al, 2008;Rosbottom et al, 2008;Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Foetal immunocompetence develops gradually through gestation, and the timing of infection in gestation is an important factor in determining the disease outcome (Maley et al 2006, Rosbottom et al 2008. In cattle, inoculation with tachyzoites during early gestation induces foetal death (Dubey et al 1992;Barr et al 1994;Williams et al 2000Williams et al , 2003Macaldowie et al 2004), whereas infections occurring later in pregnancy usually result in the birth of congenitally infected but clinically normal calves (Barr et al 1994, Williams et al 2000, Innes et al 2001, Maley et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…N. caninum multiplication during pregnancy may increase Th1-type cytokines, which could contribute to foetal death due to immune-mediated pathological alterations (Innes et al 2002, Quinn et al 2002a; however, few studies have explored this hypothesis. In cattle, N. caninum infection in early gestation, which results in foetal death, has been found to be associated with a much greater increase in placental Th1-and Th2-type cytokine expression, placental necrosis, and inflammatory cell infiltration compared to cattle infected later in gestation, when the foetus survives (Rosbottom et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Foi sugerido que o tempo da resposta Th1 durante a gestação é crítico para a sobrevivência fetal e assim a resposta IFNγ, induzida pela infecção com N. caninum no final da gestação, pode ter ocorrido tarde demais para afetar uma resposta Th2 bem estabelecida na interface materno-fetal. Rosbottom et al (2008) …”
Section: Abortamentounclassified